PEMODELAN BAWAH PERMUKAAN GUNUNG MERAPI MENGGUNAKAN METODE GRAVITASI BERDASARKAN DATA TAHUN 2011 - , LUTFI AZIZA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Geophysical study by applying gravity method has been conducted to make subsurface modelling of Merapi Volcano. The data used in this study is the data obtained from a survey in 2011. The study area covers an area of 26.9 km x 23.2 km with 198 measurement points. Complete Bouguer anomaly was transformed into a horizontal plane based on Dampney method, with the height of the horizontal plane is 3000 m and the depth of equivalent mass is 6000 m. The regional and residual anomalies were separated by using moving average method. The moving window is 39 x 41 wide. Modelling performed on the residual anomaly concerning on four slices. Subsurface condition of Merapi Volcano consist of the product of Pra Merapi with density of 2,8 gr/cc, Old Merapi with density of 2,75 gr/cc, Middle Merapi with density of 2,5 gr/cc, New Merapi with density of 2,45 gr/cc, and Tertiary marine facies rock with density of 2,45 gr/cc. Shallow magma pocket with density of 2,2 gr/cc is found at the depth of 1600 m until 2200 m below the submit, with the length of its vertical radius is about 600 m and horizontal radius is about 800 m. A vertical pipe connects the magma pocket with the submit part and magma chamber.